Production of ’Anão Verde’ coconut irrigated with saline water - Marinho, Francisco José Loureiro; Gheyi, Hans Raj; Fernandes, Pedro Dantas; Holanda, José Simplício de; Neto, Miguel Ferreira (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the viability of the use of saline water for irrigating coconut (Cocos nucifera L.) cv. Anão Verde in a 3.5 years-old plantation, at the initial phase of production. A completely randomized block design, consisting of four levels of water salinity (electrical conductivity – ECw = 0.1, 5.0, 10.0 and 15.0 dS m-1 at 25ºC), was adopted with five replications. Female flowers in inflorescence showed a tendency to enhance when salt was added to irrigation water. The use of saline waters with ECw>5.0 dS m-1 caused significant reductions in mean weight and number of fruits compared to control (ECw = 0.1 dS m-1) starting, respectively, at 11th and 14th harvest of fruits. Plants irrigated with saline waters of ECw up to 10.0 dS m-1 present acceptable mean yield for the studied crop stage.